Kontrak Sosial Dalam Pemikiran Politik Sunni - Muhammad Misbahuddin (Al-Adabiya: Jurnal Kebudayaan dan Keagamaan, 2018)
Society in the modern world is known as a group of individuals built on a social contract. In order to create a nation-state. Nevertheless, long before Europe imposed a social contract for the construction of a nation-state, Islam has long ruled its people in one state. The Madinah Charter has become the source of the law in the regulation of the early Islamic society. Political divisions in Islam do not erode the concept of social contract, but they are becoming stronger and more pervasive in existing political groups.